2016
DOI: 10.1186/s13034-016-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse and personality disorder comorbidity in adolescent outpatients: are girls more severely ill than boys?

Abstract: BackgroundSubstance use disorders (SUDs) constitute a major health problem and are associated with an extensive psychiatric comorbidity. Personality disorders (PDs) and SUDs commonly co-occur. Comorbid PD is characterized by more severe addiction problems and by an unfavorable clinical outcome. The present study investigated the prevalence of SUDs, PDs and common Axis I disorders in a sample of adolescent outpatients. We also investigated the association between PDs and SUDs, and how this association was influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 62 publications
1
13
0
1
Order By: Relevance
“…A strong association was observed between impulsivity and reduced thought processes prior to relapse implying that relapse is impulsive and most of the addicts never thought about the effort made during remission. Illicit drugs are believed to raise impulsivity ( Adinoff et al., 2007 ; Perry and Carroll, 2008 ); latter being a trait observed in individuals with personality disorders such as antisocial personality disorder (ASPD) or borderline personality disorder (BPD) ( Jahng et al., 2011 ; Korsgaard et al., 2016 ; Martin et al., 2019 ). Research has shown that up to 23% and 53% of patients suffering from ASPD and BPD respectively are strongly linked to SUD.…”
Section: Discussionmentioning
confidence: 99%
“…A strong association was observed between impulsivity and reduced thought processes prior to relapse implying that relapse is impulsive and most of the addicts never thought about the effort made during remission. Illicit drugs are believed to raise impulsivity ( Adinoff et al., 2007 ; Perry and Carroll, 2008 ); latter being a trait observed in individuals with personality disorders such as antisocial personality disorder (ASPD) or borderline personality disorder (BPD) ( Jahng et al., 2011 ; Korsgaard et al., 2016 ; Martin et al., 2019 ). Research has shown that up to 23% and 53% of patients suffering from ASPD and BPD respectively are strongly linked to SUD.…”
Section: Discussionmentioning
confidence: 99%
“…That some hyperactivity-impulsivity associations were more pronounced for females is supported by evidence that females may require greater exposure to genetic and environmental risks for ADHD (Taylor et al, 2016) and alcoholism (Foster et al, 2015) to develop. For instance, higher ADHD prevalence has been observed for female than male adolescents presenting with alcohol or marijuana use disorders (Korsgaard et al, 2016). Preliminary evidence suggests impulsivity may predict greater induced alcohol craving among young women than men (Yarmush et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other opioids, including heroin, are used as recreational drugs and have the ability to induce opioid dependence. Substance use disorder is classified as a chronic recurrent disease of the central nervous system (CNS) which leads to personality disorders, co-morbidities and premature death [2,3]. Substance use disorder develops as a result of long-term administration of substances with abuse potential and include physical dependence and/or psychological addiction.…”
Section: Introductionmentioning
confidence: 99%